IMF-Supported Programs in Low Income Countries : Economic Impact over the Short and Longer Term - Mumssen, Christian (IMF Working Papers; Working Paper ;, 2013)
This paper studies the short and longer-term impact of IMF engagement in Low-Income Countries (LICs) over nearly three decades. In contrast to earlier studies, we focus on a sample composed exclusively of LICs and disentangle the different effects of IMF longer-term engagement and short-term financing using a propensity score matching approach to control for selection bias. Our results indicate that longer-term IMF support (at least five years of program engagement per decade) helped LICs sustain economic growth and boost resilience by building fiscal buffers. Interestingly, the size of IMF financing has no significant impact on economic growth, possibly pointing to the prominent role of IMF policy advice and institutional capacity building in the context of longer-term engagement. We also present evidence that the short-term IMF engagement through augmentations of existing programs or short-term and emergency facilities is positively associated with a wide range of macroeconomic outcomes. Notably, the IMF financial support has the greatest impact on short-term growth when LICs are faced with substantial macroeconomic imbalances or exogenous shocks.